Social justice perceptions of teacher candidates - Turhan, Muhammed (My University, 2010)
This study aims to determine the social justice perceptions of teacher candidates being trained in an education faculty. For this purpose, national and international literature was reviewed by the researcher and a 32-item questionnaire was developed and implemented on 237 senior year education faculty students. Data from the questionnaires were analyzed and social perception judgment was concluded to have a four dimensional structure; behaving in line with the principle of equality, social sensitivity, social responsibility and discrimination perception. It was found that teacher candidates had high social sensitivity, but relatively lower social responsibility levels and equality behaviors. The analyses showed that their social justice perceptions differed meaningfully with respect to gender and their major area of study. © 2010 Academic Journals.
Keywords: Social justice; Social justice in education; Social justice perceptions